167k views
5 votes
Help please out due to medical issues trying to catch up and learn for my upcoming test

Help please out due to medical issues trying to catch up and learn for my upcoming-example-1
User Ardaar
by
5.6k points

1 Answer

6 votes

Answer:

The functions given in the question are


f(x)=7x-7,g(x)=x^2-7x+6

Step 1:

To figure out (fog)(x), we will substitute the value of x=x²-7x+6 in f(x)


\begin{gathered} f(x)=7x-7, \\ f(g)(x)=7(x^2-7x+6)-7 \\ f(g)(x)=7x^2-49x+42-7 \\ f(g)(x)=7x^2-49x+35 \end{gathered}

Hence,

The function for (fog)(x) will be


\Rightarrow7x^2-49x+35

Step 2:

To figure out (gof)(x), we will substitute the value of x=7x-7in g(x)


\begin{gathered} g(x)=x^2-7x+6 \\ g(f(x)=(7x-7)^2-7(7x-7)+6 \\ g(f(x)=(7x-7)(7x-7)-49x+49+6 \\ g(f(x)=49x^2-49x-49x+49-49x+49+6 \\ g(f(x)=49x^2-147x+104 \end{gathered}

Hence,

The value for (gof)(x) will be


\Rightarrow49x^2-147x+104

User Yevgeniy Gendelman
by
6.5k points